Sexualidad y gnero - Crisanto Castro, Jaime Elmer (2020)
This study on professional sufficiency has as components Identity and personality, of which specific topic is Sexuality and Gender. The study, mentioned above, will be carried out in Peru, La Libertad region, Trujillo district, at 'Mentes Brillantes-San Isidro' private school specifically the first grade 'A'. It presents three different aspects which, in turn, are interrelated. In regard to the first aspect we have: the planning, the carry out and evaluation of lesson plan; in the second aspect we have the theoretical support, according to the topic Sexuality and Gender. Regarding Sexuality we have developed the historical aspect, pedagogies, definitions and the way in which it should be understood, treated by parents, teachers toward the children or students. In respect to Gender, we have developed the Gender approach, definition, development, Gender building, gender roles. With regard to the last aspect, we have been dealing with the pedagogical support of the pedagogical strategies such as: Motivation, previous knowledge, cognitive conflict; data processing, evaluation and Meta-cognition.